Play production today - Mobley, Jonnie Patricia (National Textbook Co., 1996)
The book offers a step-by-step production process by taking an in depth look at the many jobs to be done in mounting a show from the formation of the company through auditions and rehearsals to the final performance. Chapters give preview of topics and working vocabulary, an overview of theatre history from antiquity to the contemporary stage, profiles of theater professionals, and a variety of activities designed to encourage personal creativity and foster communication and cooperation.